Enhancing Concept Comprehension and Recall through Imagery: The Case for International Students - C. Jane Edwards (Universitas Negeri Surabaya, 2013)
Teaching new marketing concepts to international students (from non-native speaking backgrounds) often poses challenges for lecturers. Past assessment results show that brand development strategies are poorly understood by international students studying a marketing principles course at an Australian tertiary institution. Students find difficulties in conceptualising the various brand development strategies via purely written and verbal description even when many examples are given. Therefore alternative pedagogical strategies are required to enhance students learning of particular concepts An empirical study, drawing upon cognitive psychology theory, was undertaken to determine whether an intervention strategy of using greater visual cues enhances international students understanding and recall of the brand extension concept. The study was conducted with two business diploma classes undertaking a first year university marketing principles course. The intervention class was taught the concept with diagrams using relevant pictorial cues. The control class was taught the same concept with diagrams alone. Both groups were tested for understanding and recall of the concept after one week. Participant test results and survey questionnaires support the hypothesis that the addition of picture cues enhances students comprehension as they mitigate the cognitive load caused by English vocabulary deficits. Picture cues prompted greater connections with students prior knowledge increasing meaning construction and the verbal and visual encoding enabled elaborate processing resulting in higher recall of the concepts. Additionally participants metacognitive reports proved the brand extension concept easier to recall when taught with imagery. These results indicate increased use of imagery can be a cost-effective strategy to enhance student learning when demonstrating new concepts to international students.